Light-field-driven current control in solids with pJ-level laser pulses at 80 MHz repetition rate - Hanus, Vaclav; Csajbok, Viktoria; Papa, Zsuzsanna; Budai, Judit; Marton, Zsuzsanna; Kiss, Gellert Zsolt; Sandor, Peter; Paul, Pallabi; Szeghalmi, Adriana; Wang, Zilong; Bergues, Boris; Kling, Matthias F.; et al. (Optica, 2021)
Future PHz electronic devices may be able to perform operations on few-femtosecond time-scales. Such devices are based on the ability to control currents induced by intense few-cycle laser pulses. Investigations of this control scheme have been based on complex, amplified laser systems, typically delivering mJ or sub-mJ-level laser pulses, limiting the achievable clock rate to the kHz regime. Here, we demonstrate transient metallization and lightwave-driven current control with 300-pJ laser pulses at 80 MHz repetition rate in dielectric media (HfO2 and fused silica), and the wide-bandgap semiconductor GaN. We determine the field strength dependence of optically induced currents in these media. Supported by a theoretical model, we show scaling behaviors that will be instrumental in the construction of PHz electronic devices.
CRIS-Team Scopus Importer:2023-04-20